Understanding the role of trehalose in interactions between Wolbachia and Aedes aegypti - Dupuis, Benjamin; Pocquet, Nicolas; Failloux, Anna-Bella (Frontiers in Cellular and Infection Microbiology, 2025)
Mosquito-borne diseases such as chikungunya, dengue, and Zika represent a major burden on global public health. To fight against these arboviruses, vector control strategies are a priority. One existing strategy is based on the use of an endosymbiotic bacterium, Wolbachia, which reduces the transmission of arboviruses by the mosquito Aedes aegypti via a pathogen blocking effect. Wolbachia in Ae. aegypti disrupts several pathways of the host’s metabolism. Trehalose is a carbohydrate circulating mainly in insect hemolymph and plays a role in numerous mechanisms as energy source or stress recovery molecule and in chitin synthesis. This study explores the importance of trehalose in the interactions between Wolbachia and Ae. aegypti, and attempts to understand the pathogen blocking effect.